Teachers’ and caretakers’ perceptions on green outdoor environment for children with learning disabilities at a primary school in Selangor, Malaysia - Abdul Aziz, Noor Azramalina (2017)
In early childhood education, extensive research has shown that young children have unique learning styles and experience in physical, emotional, social, language and cognitive will change in a predictable way that match on their stages which occur in an orderly sequence during their lives. Numerous studies has shown that the children with disabilities have a slow development in learning process. The importance of stimulating environment for children with disabilities has since been confirmed. There is a lack of research supporting evidence-based design concerning green outdoor learning environment at special education for children with learning disabilities in a Malaysian context from the past studies done. The purpose of this thesis is to identify suitable design of green outdoor environment (GOEs) that could contribute to the learning process of children with learning disabilities and at the same time support the curriculum for special education at primary schools in Malaysia. This study focuses on the type of outdoor learning environment preferred among the teachers, caretakers and special students involved in the special education at a primary school in Malaysia. Three research objectives were developed which are 1) to identify the type of outdoor learning environments preferred among the teachers, caretakers and special students,2) to analyze the preferences and 3) to provide implications for the design of GOEs for children with learning disabilities in special education at primary school. A primary school in Serdang which has a Special Education Integrated Program was selected as a case study. This study involved a sample of primary school children at special education class (7 to 14 years old) who attended the school from 7:30 to 1:00pm for 5 days a week. The children followed the standard curriculum when they were in school.This study applied a mix method which is the quantitative (questionnaire) and the qualitative (interview and behavioural observation) methods to collect the data. Asurvey form for behavioural observation was used to survey the children in order to identify their preferred activities for outdoor and indoor classroom. The teachers and caretakers were interviewed and also given questionnaires to identify the activities and the landscape design characteristics that their students preferred when being outdoor and indoor. Results from the findings have shown that children with learning disabilities preferred to be in the outdoor environment rather than in an indoor classroom. The GOEs should offer facilities that could encourage a sense of security, space for interaction and easy supervision. It should also heighten their sensory awareness and experience. The findings presented 4 divisions of the implication for GOEs which are a) the outdoor should be an attractive place, b) provide safety aspects, c) increase interaction and d) provide a transition space. Furthermore, the results have shown that GOEs have potentials to be part of therapy programmes for children with learning disabilities at primary schools in Malaysia.